2019
DOI: 10.1177/0972150919846814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dividend Tax Change on the Payout Policy of Indian Companies

Abstract: The article examines the impact of regulatory changes in the tax on dividends on the payout policy of Indian companies. The tax law was recently amended to levy tax on dividends received by large shareholders. As the promoters group is the largest shareholder, this is expected to have a negative impact on the payout policy of companies. Furthermore, companies with larger promoter holdings have a higher motivation to reduce their payout. The study covers 370 companies present in the BSE 500 Index and compares t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Promoters' holdings have a positive effect on the dividend payout of BSE 500 listed companies in India (Gupta 2017). On the contrary, companies with more than 65 to 70 per cent promoters' holdings result in having a 21.3 per cent decrease in the dividend payout ratio, due to higher tax on dividend income (Dhamija and Arora 2019). Earlier scholars reported that larger amounts of promoter holding demotivate the promoters to choose a higher payout ratio (Kumar 2006).…”
Section: Promoters' Holdings and Dividend Payout Ratiomentioning
confidence: 99%
“…Promoters' holdings have a positive effect on the dividend payout of BSE 500 listed companies in India (Gupta 2017). On the contrary, companies with more than 65 to 70 per cent promoters' holdings result in having a 21.3 per cent decrease in the dividend payout ratio, due to higher tax on dividend income (Dhamija and Arora 2019). Earlier scholars reported that larger amounts of promoter holding demotivate the promoters to choose a higher payout ratio (Kumar 2006).…”
Section: Promoters' Holdings and Dividend Payout Ratiomentioning
confidence: 99%
“…Liquidity can also positively influence dividend payouts in the context of the agency problem (Hu et al, 2020). Highly liquid firms are more likely to pay dividends than firms facing a liquidity crunch (Dhamija & Arora, 2019). Saeed et al (2014) found a positive association of liquidity with dividend payouts in the Pakistani financial sector.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…Faktor lainnya yang dapat memengaruhi kebijakan dividen adalah asset tangibility. Perusahaan dengan aset berwujud yang tinggi lebih berpeluang untuk mendapatkan pendanaan eksternal sehingga memiliki kemampuan untuk membagikan dividen (Dhamija & Arora, 2019). Kemampuan untuk mendapatkan pendanaan eksternal umumnya dimiliki oleh perusahaan besar karena memiliki kemudahan dalam akses terhadap pasar modal.…”
Section: Pendahuluanunclassified
“…Arus kas bebas yang tinggi menandakan bahwa perusahaan memiliki kas yang tersedia banyak sehingga perusahaan akan membagikan dividen (Dhamija & Arora, 2019). Hipotesis 6 diterima karena nilai signifikansi arus kas bebas bernilai 0,035 dengan nilai koefisien 0,111.…”
Section: Tabel 4 Hasil Uji Chowunclassified